This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: (c) No. If we let y ( t ) = t R- x ( ) d with x ( t ) = u ( t )-u ( t-1). Then x ( t ) = 0 for t > 1, but y ( t ) = 1 for t > 1. Problem 1.43 (a) We have x ( t ) S y ( t ) Since S is time-invariant, x ( t-T ) S y ( t-T ) Now if x ( t ) is periodic with period T, x ( t ) = x ( t-T ). Therefore, we may we conclude that y ( t ) = y ( t-T ). This implies that y ( t ) is periodic with period T . A similar argument can be made in discrete-time. (b) Consider the system y ( t ) = X k =- x 2 ( t-2 k ) The above system is time-invariant. Consider the input x ( t ) = u ( t )-u ( t-1). Then it is easy to see that while the input is not periodic, the output is periodic. 2...
View Full Document
This note was uploaded on 01/01/2012 for the course ECEN 314 taught by Professor Halverson during the Spring '08 term at Texas A&M.
- Spring '08